2009
DOI: 10.1289/ehp.11827
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic Exposure within the Korean Community (United States) Based on Dietary Behavior and Arsenic Levels in Hair, Urine, Air, and Water

Abstract: BackgroundDetermining arsenic exposure in groups based on geographic location, dietary behaviors, or lifestyles is important, as even moderate exposures may lead to health concerns.Objectives/MethodsThe Korean community in Washington State, represents a group warranting investigation, as they consume foods (e.g., shellfish, rice, finfish, and seaweed) known to contain arsenic. As part of the Arsenic Mercury Intake Biometric Study, we examined the arsenic levels in hair and urine along with the diets of 108 wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 49 publications
5
36
0
Order By: Relevance
“…category consumed the largest average amount of rice (2.2 cups/d) (23). In a 2009 study of a US Korean community, the mean cooked rice intake was 2.9 cups/d (29), and the median total urinary arsenic concentration (iAs + MMA + DMA) was more than three times the national median (21.6 μg/L vs. 6.0 μg/L) (26). Additionally, ∼3 million Americans (30) with celiac disease, an autoimmune disease triggered by gluten ingestion, may also have high levels of arsenic exposure via rice.…”
Section: Resultsmentioning
confidence: 99%
“…category consumed the largest average amount of rice (2.2 cups/d) (23). In a 2009 study of a US Korean community, the mean cooked rice intake was 2.9 cups/d (29), and the median total urinary arsenic concentration (iAs + MMA + DMA) was more than three times the national median (21.6 μg/L vs. 6.0 μg/L) (26). Additionally, ∼3 million Americans (30) with celiac disease, an autoimmune disease triggered by gluten ingestion, may also have high levels of arsenic exposure via rice.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of As and Pb absorbed by humans appears to be eliminated relatively quickly and primarily via urine. Thus, the concentrations of these metals in urine samples are important biomarkers of short-term exposure and have been used in numerous epidemiologic studies (Cleland et al 2009;McElroy et al 2008). In the present study, we found a significant relationship between urinary As levels and risk of hypertension in Taiwanese rural residents.…”
Section: Discussionmentioning
confidence: 99%
“…The background urinary As levels are 10 μg/L in European countries and in the United States, 46 and 9.1 μg/L in the control adult group in Inner Mongolia, China. 47 The urinary As concentrations in our present study at the end of the experimental cycle still exceeded the background levels after people drank the As-free groundwater.…”
Section: Environmental Science and Technologymentioning
confidence: 93%